2017
DOI: 10.2119/molmed.2016.00064
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-26 Production in Human Primary Bronchial Epithelial Cells in Response to Viral Stimulation: Modulation by Th17 cytokines

Abstract: Interleukin (IL)-26 is abundant in human airways and this cytokine is involved in the local immune response to a bacterial stimulus in vivo. Specifically, local exposure to the toll-like receptor (TLR) 4 agonist endotoxin does increase IL-26 in human airways and this cytokine potentiates chemotactic responses in human neutrophils. In addition to T-helper (Th) 17 cells, alveolar macrophages can produce IL-26, but it remains unknown whether this cytokine can also be produced in the airway mucosa per se in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
2
31
1
Order By: Relevance
“…While immunofluorescence staining of skin sections of hIL-26Tg mice indicated that IL-26 was produced by CD4-positive cells as well as other cell types, the cells involved may differ in the IMQ-induced psoriasis model from psoriasis patients (Figure 3b, 3d). In addition to Th17 cells, other IL-26eproducing cells have been identified recently (Che et al, 2014(Che et al, , 2017Corvaisier et al, 2012;Poli et al, 2017). In the skin lesions of psoriatic patients, IL-17 is produced not only from CD4 þ T cells, but also from CD8 þ T cells and gd T cells (Golden et al, 2013;Matos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While immunofluorescence staining of skin sections of hIL-26Tg mice indicated that IL-26 was produced by CD4-positive cells as well as other cell types, the cells involved may differ in the IMQ-induced psoriasis model from psoriasis patients (Figure 3b, 3d). In addition to Th17 cells, other IL-26eproducing cells have been identified recently (Che et al, 2014(Che et al, , 2017Corvaisier et al, 2012;Poli et al, 2017). In the skin lesions of psoriatic patients, IL-17 is produced not only from CD4 þ T cells, but also from CD8 þ T cells and gd T cells (Golden et al, 2013;Matos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We think that this can be explained as follows: Extracellular IL-26 protein in BAL samples reflects the production and release from several cellular sources, including structural cells such as bronchial epithelial cells and lung fibroblasts, as well as leukocytes. 4,8,9 In contrast, the IL-26 mRNA that we quantified to assess gene expression is likely to originate exclusively from luminal leukocytes in the airways.…”
Section: To the Editormentioning
confidence: 99%
“…41 Viral stimulation of bronchial epithelial cells induces IL-26 production that is enhanced by IL-17, suggesting a role to IL-26 in asthma attacks. 18 In the same way, modifications of airways microbiota have been reported in severe asthma, together with a possible role of bacteria in the severity of asthma. 42,43 The role of macrophages, which are a prominent source of IL-26 during activation of anti-bacterial host defense, should be more deeply investigated.…”
Section: Discussionmentioning
confidence: 75%
“…Several resident and inflammatory pulmonary cells express and release IL-26. 14,18 A local production has been demonstrated by bronchial and lung biopsies with immunostaining of bronchial epithelial cells and macrophages/ monocytes. 35 Lung fibroblasts participate as well to IL26 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation